2014
DOI: 10.1371/journal.pone.0113398
|View full text |Cite|
|
Sign up to set email alerts
|

Berberine Improves Kidney Function in Diabetic Mice via AMPK Activation

Abstract: Diabetic nephropathy is a major cause of morbidity and mortality in diabetic patients. Effective therapies to prevent the development of this disease are required. Berberine (BBR) has several preventive effects on diabetes and its complications. However, the molecular mechanism of BBR on kidney function in diabetes is not well defined. Here, we reported that activation of AMP-activated protein kinase (AMPK) is required for BBR-induced improvement of kidney function in vivo. AMPK phosphorylation and activity, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…These data suggested that the rat model of DN was successfully established (Betz and Conway, 2014). After treatment with berberine, the physiological indicators in the cases showed varying degrees of improvement (Zhao et al, 2014). The data above also suggested that berberine could not only reduce the blood glucose and urine total protein excretion except for the body weight but also improve the renal pathological changes, such as ECM accumulation, glomerulus atrophy and glomerular sclerosis, thus preventing the progression of DN .…”
Section: Discussionmentioning
confidence: 83%
“…These data suggested that the rat model of DN was successfully established (Betz and Conway, 2014). After treatment with berberine, the physiological indicators in the cases showed varying degrees of improvement (Zhao et al, 2014). The data above also suggested that berberine could not only reduce the blood glucose and urine total protein excretion except for the body weight but also improve the renal pathological changes, such as ECM accumulation, glomerulus atrophy and glomerular sclerosis, thus preventing the progression of DN .…”
Section: Discussionmentioning
confidence: 83%
“…Some studies showed that AMPK inactivation was linked to low levels of oxidative stress, and that AMPK activation reversed these effects [41,42]. However, other studies demonstrated that AMPK inactivation was closely related to increased oxidative stress, and that AMPK reactivation decreased levels of oxidative stress [22,[43][44][45][46]. In this study, our results showed that HG-induced oxidative stress was closely related to downregulation of AMPKα1 expression.…”
Section: Overexpression Of Ampkα1 Is Essential For Protective Effect mentioning
confidence: 41%
“…Recently, dysregulation of AMP-activated protein kinase (AMPKα1) signaling has been implicated in oxidative stress-induced vascular and kidney dysfunction [20][21][22]. Although the effects of miR-137 have been linked to oxidative stress [23], the effects of miR-137 and its precise mechanisms remain incompletely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Berberine may also protect the kidney from injury by modulating the EP4‐Gαs‐cAMP signalling pathway . Activation of AMP‐activated protein kinase is largely involved in the renoprotective effects of berberine …”
Section: Underlying Mechanisms Of Chinese Herbal Medicines In Treatinmentioning
confidence: 99%